Psychomotor Tremor and Proprioceptive Control Problems in Current and Former Stimulant Drug Users: An Accelerometer Study of Heavy Users of Amphetamine, MDMA, and Other Recreational Stimulants. (19th April 2017) - Downey, Luke A.; Tysse, Brenda; Ford, Talitha C.; Samuels, Angela C.; Wilson, Rory P.; Parrott, Andrew C.
Abstract: The recreational use of various stimulant drugs has been implicated in the development of movement disorders through dysregulation of the dopaminergic and serotoninergic neurotransmitter systems. The present study investigated psychomotor differences in current and former recreational stimulant drug users compared with nonusing controls. Sixty participants comprised 3 groups: 20 current stimulant drug users (CSUs; 11 men, aged 31.4 ± 9.1 years), 20 former stimulant drug users (FSUs; 5 men, aged 39.1 ± 8.5 years), and 20 nonuser controls (NUCs; 5 men, aged 35.7 ± 6.4 years). Psychomotor arm steadiness for each participant was assessed with a wrist‐attached accelerometer during 5 arm positions with eyes open and then eyes closed. Arm‐drop of arm position was indicated by the arm longitudinal rotation axis (ALoRA), and tremor was indicated by the overall vector of dynamic body acceleration (VeDBA). Overall, CSUs performed the most poorly on ALoRA ( P < .05) and VeDBA indices ( P < .05), and FSUs perform almost as poorly on VeDBA indices ( P < .05) compared with NUCs. It was concluded that stimulant drug use, primarily MDMA and amphetamines, may result in acute stimulant‐induced tremor as well as long‐term proprioceptive deficits in terms of arm‐droop.